2013
DOI: 10.1121/1.4824122
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic waveguiding by pliable conduits with axial cross sections as linear waveguides in two-dimensional sonic crystals

Abstract: Pliable conduits composed of periodically arranged concentric aluminum tori in air, with their axial cross sections acting as linear waveguides in two-dimensional sonic crystals, are numerically shown to guide acoustic waves in three dimensions in a flexible manner. Waveguide band structures are obtained by exploiting axial symmetry in a super-cell approach through two-dimensional finite-element simulations under the periodic boundary conditions. One isolated band having a bandwidth of 19.66% or 10.10% is obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Moreover, gradient-index PnCs, in which the effective index over the PnC is a function of position, can also be used to steer acoustic waves by 90 degrees through a smooth bend by gradually rotating anisotropic scatterers [19] or gradually varying the scatterer sizes across the bend [20]. A more recent approach facilitates wave transmission between two arbitrary points through smooth bends of radially symmetric PnCs where low-loss transmission up to a 180 degree bend is demonstrated [21].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, gradient-index PnCs, in which the effective index over the PnC is a function of position, can also be used to steer acoustic waves by 90 degrees through a smooth bend by gradually rotating anisotropic scatterers [19] or gradually varying the scatterer sizes across the bend [20]. A more recent approach facilitates wave transmission between two arbitrary points through smooth bends of radially symmetric PnCs where low-loss transmission up to a 180 degree bend is demonstrated [21].…”
Section: Introductionmentioning
confidence: 99%
“…5) Cicek et al extended this effect to 3D scenarios to guide acoustic waves in a flexible manner. 6) The sub-diffraction (or self-collimation) effect, namely suppressing the diffraction of light, has been carried out in 2D photonic crystals, 7) which also exist in 2D SCs. Víctor et al first demonstrated the self-collimation propagation of sound beams in a 2D SC.…”
mentioning
confidence: 99%